Fibroepithelioma of Pinkus Revisited. Issue 3 (September 2016) - Haddock, Ellen; Cohen, Philip
Abstract Background Fibroepithelioma of Pinkus (FeP) is considered a variant of basal cell carcinoma (BCC); however, in the past 20 years, some researchers have argued for its classification as a trichoblastoma. Recently, use of a new immunostaining marker and further dermoscopic characterization of FeP have advanced the debate about its proper classification. Purpose A review of the evidence for and against classification of FeP as BCC or trichoblastoma is presented. Methods Using PubMed, the term FeP was searched and relevant citations were assessed. Additional relevant articles were identified from references of key papers. Results FeP shares characteristics of both trichoblastoma and BCC. Conclusion Derived from the same cell type, BCC and trichoblastoma may be best considered as representing opposite ends of a spectrum of differentiation, with FeP deserving an intermediate classification.